Communication in our lives - Wood, Julia T. (Boston, MA, USA Cengage Learning, 2018)
Communication in our lives, 8th Edition, gives students what they need to strengthen interpersonal, group, public speaking, and media literacy skills. Award-winning scholar Julia T. Wood combines skills development with the latest research and theory of communication scholars. Praised by instructors and students, this product features a highly readable style and Student Voice sections. This edition integrates social and cultural diversity, emphasizes public speaking, expands coverage of mass and social media, and includes a new focus on health communication. Online study tools allow you to customize the content and help your students become more confident and effective communicators.
Part I. Foundations of communication. The world of communication ; Perception and communication ; Communication and personal identity ; Listening effectively ; The verbal dimension of communication -- Part II. Contexts of interaction. The nonverbal dimension of communication ; Communication in personal relationships ; Communication in groups and teams ; Communication in organizations ; Communication and culture ; Media and media literacy -- Part III. Public communication. Planning public speaking ; Researching and developing support for public speeches ; Organizing and presenting public speeches ; Informative speaking ; Persuasive speaking.
Includes bibliographical references (pages [373]-388) and index.
Keywords: Communication; Interpersonal communication; Public speaking